Investigation of the Parametric Vibrations of Laminated Plates by RFM - Kurpa, Lidiya; Mazur, Olga; Tkachenko, Victoria (NTU "KhPI", 2016)
The R-functions theory is applied to study free vibration and dynamic instability of the symmetrically laminated plates subjected to combined static and periodic axial forces. It is assumed that subcritical state of the plate may be inhomogeneous. Theoretical formulation is made on the classical plate theory (CTP). The developed approach is based on combined application of Ritz’s method, Galerkin procedure, R-functions theory and Bolotin’s method. The buckling, instability zones and response curves for laminated plate with different external cutouts are presented and discussed. Effects of plate geometrical parameters, parking of layers, mechanical characteristics of the material on buckling, natural frequencies and parametric resonance are also studied.
Keywords: parametric vibrations; R-functions theory; laminated plates